Interrelationships among Genera of Cyprinidae (Teleostei) as Indicated by the Caudal Skeleton - Kotalawala, A.B. (My University, 1991)
The studies on the osteology of caudal skeleton and the ray counts showed that the twenty one species of Cyprinidae studied fall into three groups, one containing four species, the other with 16 species and third group with one species. The first group with four species has the most primitive type of caudal skeleton containing six free hypurals, three epurals and sixteen or more branched rays. The second group which is the major group with sixteen species has lesser primitive type of caudal skeleton with six hyupurals, two epurals and sixteen or more branched rays. The third group with one species has an advanced caudal skeleton with five free hypurals, two epurals and fifteen or sixteen branched rays.
Keywords: Caudal skeleton; Hypurals; Epurals; Parhypural; Uroneurals